ダイ40ジ ナンキョク チイキ カンソクタイ キショウ ブモン ホウコク 1999 - 東島, 圭志郎; ヒガシジマ, ケイシロウ; 佐藤, 建; サトウ, タケル; 安ヶ平, 一也; ヤスガヒラ, カズヤ; 村方, 栄真; ムラカタ, エイシン; 河原, 恭一; カワハラ, キョウイチ; Higashijima, Keishiro; Sato, Tatsuru; et al. (2003)
P(論文) これは,第40次南極地域観測隊気象部門が,1999年2月1日から2000年1月31日まで,南極昭和基地において気象観測を行った結果の報告である.気象観測の方法,測器,統計方法等は,第39次隊とほぼ同様である. 越冬期間中,特記される気象現象として,次のものがあげられる.1) 地上気象観測において,7月,12月,1月の気温,5月,10月,12月,1月の気圧が平年に比べ著しく低かった.10月5日に最低海面気圧932.1hPa(歴代2位)を記録した.ブリザードは,A級が4回,B級が10回,C級が11回の計25回あり,平年並みであった.2) オゾン全量観測において,昨年に引き続き大規模なオゾンホールを観測し,11月の月平均オゾン全量は過去最低を記録した.その後,12月中旬にオゾンホールは消滅したが,オゾン全量値の回復は過去一番遅かった.3) それに伴い,成層圏の昇温が遅れ,春季に下部成層圏で記録的に低い月平均気温を観測した.4) エアロゾルゾンデ観測において,春期南極上空で形成されるオゾンホールの重要要因となっていると思われる極成層圏雲(PSCs)の雲粒子の分布状況を観測した.5) 地上オゾン濃度観測において,観測を始めた第38次隊以来連続して地上オゾン濃度急減現象を観測した. This report presents the results of meteorological observations at Syowa Station from February 1, 1999 through January 31, 2000, carried out by the 40th Japanese Antarctic Research Expedition (JARE-40). The meteorological observation method, measuring instruments, means to compile statistics, and other aspects of the work were almost the same as those used by the 39th Japanese Antarctic Research Expedition. Remarkable weather phenomena during the wintering period are as follows: 1) In the surface weather observations, in July, December and January, the atmospheric temperature was significantly lower recorded compared to normal average years, and also the atmospheric pressure was significantly lower in May, October, December and January. The lowest sea level pressure, 932.1hPa was recorded during a severe blizzard on October 5 for the JARE-40 period (the 2nd lowest in history). There were 25-blizzards of which 4 were class A, 10 class B, and 11 class C, the same level as in a normal year.2) As a result of total ozone observation, the large-scale ozone hole was observed, as in the previous year, and the monthly average amount of total ozone in November recorded the lowest ever. Then, the ozone hole disappeared in mid-December, however, the recovery of the total amount of ozone was the slowest in years.3) Because, the temperature rise for the stratosphere was delayed, record-low monthly average temperature was observed in the lower stratosphere in springtime.4) By ...